Trends in the Development of Biotechnical Systems in Animal Husbandry - V. V. Kirsanov; Yu. A. Tsoy (Сельскохозяйственные машины и технологии, 2020)
The concept of biotechnical systems belongs to the class of human-machine systems or human–machine–plant systems, human–machine–animal systems. The latter relate to agriculture and the livestock industry. In agricultural production, biotechnical systems have the properties of bimodality, when there are two or more biological objects, a person as a managing operator and a service object (plants, animals).(Research purpose) The research purpose is in analyzing trends in the development of biomachine and technical systems in order to further intellectualize and digitalize agricultural production.(Materials and methods) There are two approaches in the study of human-machine systems: anthropocentric and machine-centric; the first one assigns a crucial role to the person, the second one – to the machine.(Results and discussion) The article presents the functionality of the Human and Machine subsystems. Part of the functions of the Human operator will gradually be transferred to the Machine, and the Human operator will be transformed into a human Expert and a human User. The article presents a scheme for an intelligent biotechnical system in animal husbandry, and determines the coefficients of adaptation of local automated and robotic biotechnical systems to biological objects. Authors have created a scheme for the functioning of local biotechnical systems in a partially autonomous multi-agent control mode, and identifies criteria for evaluating the functioning of local biotechnical systems.(Conclusions) We need to strengthen the Machine factor on the basis of developing machine-centric models and convert complex three-tier system of biotech in animal husbandry in two-tier with the polarization of the human Expert, human User and Machine–Animal subsystems. The latter absorbs more and more intelligent functions that are passed by a Man, for which it retained control, coordination and management of the entire system.